Aerial Reconnaissance for Large Scale Forest Resources Survey - Seth, V. K.; Tomar, M. S. (Indian Forester, 1970)
Useful experience was gained in the Preinvestment Survey of Forest Resources Organization in carrying out aerial reconnaissance with a fixed wing plane and helicopters, in the forests of Central and Southern Zones in Bastar District of Madhya Pradesh and Kerala State. The overall cost of aerial reconnaissance would not exceed 0.4 paise per hectare or Re. 0.40 per square kilometre. Considering this low figure or cost and the mass of useful information that is obtained from an aerial reconnaissance, it would be worthwhile to carry out an aerial reconnaissance of the forested area of India. This could be achieved within 150 flying hours and an expenditure of Rs.200,000.